Fundamentals of investment : a practitioner's guide - O'Loughlin, Brian; O'Brien, Frank (London ; New York : Routledge, Taylor & Francis Group, 2019)
"Post the Financial Crash, the role of regulation and the impact of regulation on all aspects of the financial industry has broadened and intensified. Investment knowledge is a core competence required by large numbers of organisations and individuals in the financial services industry. This book builds upon the authors' predecessor book, 'Fundamentals of Investment - an Irish Perspective', and offers a comprehensive review of the operations of the industry post-financial crisis, from a variety of perspectives. The core of the original text is retained particularly concerning fundamental concepts such as discounted cash flow valuation techniques. It is, however, a new text driven by two important factors. First, the long shadow of the Global Financial Crisis and the ensuing Great Recession continues to impact economies and financial markets. Second, the new text adopts a more international perspective with a focus on the UK and Ireland. The authors present the reader with a clear linkage between investment theory and concepts (the 'fundamentals') and the practical application of these concepts to the financial planning and advisory process. This practical perspective is driven by the decades long fund management and stock broking experience of the authors. This new edition will be of particular interest to financial advisers, financial planners and those engaged in advisory and/or support functions across the investment industry. Those taking investment modules in 3rd level educational institutes will find this book to be a useful complement to the more academically focused textbooks"--
Revised edition.
BBS
Parama
Keywords: Investments; Investment analysis; Business & finance